P.017 Optimization of acute treatment and headache-related impact following eptinezumab initiated during a migraine attack: post hoc analysis of the RELIEF study. (June 2022) - Buse, DC; Lipton, RB; Ettrup, A; Josiassen, MK; Lindsten, A; Cady, R; Omeragic, A; Duong, A
Abstract : Background: Patients administered eptinezumab during an active migraine had larger numerical improvement in the 6-item Migraine Treatment Optimization Questionnaire (mTOQ-6) total score compared to placebo. The mTOQ-6 was used to determine success of acute treatment. Methods: RELIEF (NCT04152083) was a double-blind trial that randomized adults eligible for preventive migraine treatment to eptinezumab 100mg or placebo, administered intravenously within 1–6 hours of migraine onset. mTOQ-6 was captured at baseline and Week 4 and rescored into mTOQ-4. Patients were grouped by baseline mTOQ-4 total scores. Results: 226 eptinezumab-treated and 232 placebo patients were included. The percentage of patients in the combined very poor and poor optimization subgroups at baseline with eptinezumab (n=155; 68.6%) versus placebo (n=138; 59.5%) decreased by 26.6 percentage points (n=95; 42.0%) and 9.9 percentage points (n=115; 49.6%), respectively, at Week 4. Of the 155 eptinezumab-treated and 138 placebo patients who were very poorly/poorly optimized at baseline, 73 (47.1%) versus 35 (25.4%) were moderately/maximally optimized at Week 4, respectively. Greater improvements in mTOQ-6 scores were noted in patients more poorly optimized at baseline than those more optimized. Conclusions: Eptinezumab showed greater acute migraine medication optimization and decreased headache-related impact compared to placebo, suggesting that eptinezumab may work synergistically with acute medications.